2022
DOI: 10.18502/ijaai.v21i4.10295
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Chronic Granulomatosis Disease: A Case Report

Abstract: A novel coronavirus disease known as Coronavirus Disease 2019 (COVID-19) has spread quickly throughout the world, and it was declared a pandemic in March 2022. Chronic granulomatous disease (CGD) is a diverse group of genetic disorders characterized by recurrent bacterial and fungal infections, resulting in granulomas due to the inability of phagocytes to destroy microbes. Even though it is thought that impaired neutrophil activity is a protective mechanism against severe COVID-19-induced cytokine storms and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…The detailed characteristics of the included studies are shown in Additional file 2 : Table S3. There were 73 case report [ 4 6 , 8 , 9 , 25 32 , 37 39 , 44 , 45 , 49 , 51 , 53 60 , 67 69 , 72 , 76 79 , 82 84 , 86 88 , 90 , 91 , 93 , 94 , 96 , 99 107 , 109 114 , 116 , 119 123 , 126 , 127 , 129 – 131 ], 38 cohort [ 7 , 10 , 19 , 33 – 36 , 40 43 , 46 48 , 50 , 52 , 61 66 , 70 , 71 , 73 , 74 , 80 , 81 , 92 , 95 , 97 , 98 , 108 , 117 , 118 , 124 , 125 , 132 ], 4...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed characteristics of the included studies are shown in Additional file 2 : Table S3. There were 73 case report [ 4 6 , 8 , 9 , 25 32 , 37 39 , 44 , 45 , 49 , 51 , 53 60 , 67 69 , 72 , 76 79 , 82 84 , 86 88 , 90 , 91 , 93 , 94 , 96 , 99 107 , 109 114 , 116 , 119 123 , 126 , 127 , 129 – 131 ], 38 cohort [ 7 , 10 , 19 , 33 – 36 , 40 43 , 46 48 , 50 , 52 , 61 66 , 70 , 71 , 73 , 74 , 80 , 81 , 92 , 95 , 97 , 98 , 108 , 117 , 118 , 124 , 125 , 132 ], 4...…”
Section: Resultsmentioning
confidence: 99%
“…Phagocytic diseases were the sixth most-common IEIs in children who experienced COVID-19 (n = 54, 7.6%) [ 19 , 40 , 43 , 46 , 48 , 52 , 53 , 61 63 , 65 , 74 , 77 , 81 , 90 , 92 , 95 , 98 , 101 , 107 , 117 , 124 , 127 ] (see Additional file 2 : Table S3). Among them, 26 have chronic granulomatous disease (48.1% of all phagocytic diseases) [ 40 , 43 , 46 , 48 , 53 , 62 , 65 , 74 , 81 , 90 , 92 , 95 , 98 , 124 ], 8 have Shwachman-Diamond syndromes (14.8%) [ 61 , 95 , 101 ], 6 have HAX1 deficiencies (11.1%) [ 74 , 77 , 124 ], 2 have Glycogen storage diseases type 1b (3.7%) [ 62 ], and 2 have Elastase deficiency (3.7%) [ 81 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesized that defective respiratory burst and impaired neutrophil extracellular trap formation in CGD may prevent exaggerated lung tissue damage seen in severe COVID-19 infection, and probably has led to better outcomes in this subset of IEIs [ 39 ]. Nevertheless, complications including mortalities have also been reported in certain studies [ 40 42 ]. Castano‐Jaramillo et al reported a fatal MIS-C-like illness in a 16-year-old boy with CYBB mutation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CGD patients have normal immunity to most viruses. Two patients with severe COVID-19 have been reported in the literature, which suggests that COVID-19 might have a different pathogenesis than other viruses [ 46 ].…”
Section: Pathogens and Cgd-related Infectious Diseasesmentioning
confidence: 99%